The role of the martingales in the stochastic models - rrezaeyan, R. (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The stochastic model is one of the most efficient models in the stock price modeling. The martingales have the important role in this the stochastic models.The martingale theory is used for calculating the probability of the bankruptcy in the stochastic model of stock market and the stochastic model of insurance risk. In this here, we will provide an introduction to the martingale from applied point of view in the stochastic differential equations